The growth drivers of start-up firms and business modelling - Balboni, Bernardo (Management, 2014)
This paper represents the first step of a broader research project focusing on the growth performance of start-up firms in technological sectors. While our main assumption is that the growth of such firms can be mostly attributed to strategic factors, we aim at reviewing the available literature on the topic with a broader scope, with the purpose of identifying the different determinants of new firms% growth. After summarising the most relevant research perspectives on the theme, we introduce the perspective of the business model. In our view, this construct represents a significant conceptual improvement for the study and explanation of the developmental processes and performances of new ventures in hightech and science-based fields. We first define what a business model is, according to the extant literature, and then discuss the implications of the adoption of such a concept for our research. We conclude the paper by describing the research path ahead.
Keywords: podjetja; poslovni modeli; rast; razvoj; technology; tehnologija